Modelagem matemática gráfica : instigando o senso criativo dos estudantes do ensino fundamental - Brites, Elisa Maria Almeida (2012)
This Master thesis aims to analyze the possibilities of mathematical modeling graphically, through the production of drawings, to instill a sense of a creative group of 72 elementary school students. Therefore it was necessary to answer the following question: How mathematical modeling graphics can instill a sense of creative students from elementary school? For this, (1º) made a study of concepts and recent research on Mathematical Modeling Graphics, Design and Creative Child Sense to locate and acquire information to prepare a pedagogical activity, (2º) was applied to this activity during a quarter in a public school in Porto Alegre (RS), recording all oral and graphic expressions during the meetings related to activity, (3º) was made a close study of theory and test of figural Torrance (1915-2003), adapted by Wechsler (2004) on creativity. To analyze the creative sense, we used some of the test criteria of Torrance (1976) including: originality, elaboration, expression of emotion, color images, the internal perspective, unusual perspective, fantasy, action or expression of movement and creation of context. The research result showed that use of mathematical modeling graphically, allowed students to better understand the mathematical concepts learned to value their skills, to appreciate the ways different modes of expression, to represent the medium without inhibiting the spontaneity and instilled a sense creative.